Impacts of large-scale forestry investments on neighboring small-scale agriculture in northern Mozambique - Cristina Chiarella; Philippe Rufin; Dilini Abeygunawardane; Adia Bey; Sá Nogueira Lisboa; Helder Zavale; Patrick Meyfroidt (Land Use Policy, 2024)
Forestry plantations can potentially foster rural development and mitigate environmental threats, but their impacts on neighboring peoples' livelihood strategies are ambiguous. Forestry plantations are particularly important in Mozambique, where a national strategy aims to establish one million hectares of forests by 2030, focusing on Miombo ecoregions in the provinces of Niassa, Cabo Delgado, Nampula and Zambezia. This paper evaluates the causal effects of large-scale forestry investments in northern Mozambique on smallholders' farm size, crop productivity, and employment. We take advantage of a remote sensing approach that produced maps of forestry plantations and their expansion trajectories from 2001 to 2017 and combine them with data from two georeferenced nationally-representative agricultural surveys administered in 2007 and 2017. Using a difference-in-difference approach, we evaluate the effects of exposure to forestry plantations established after 2007, defined by the presence of newly established and expansion of existing plantations and their distance to households within a 20-km buffer. We find that households exposed to forestry plantations increased their planted areas but did not change hired farm employment, which was accompanied by a decrease in crop yields. The heads of households close to forestry plantations were also less likely to work in agriculture as their main activity, especially as salary workers, and more likely to be self-employed and employed in the nonfarm sector. This study contributes to an improved understanding of local dynamics resulting from forestry investments, which have critical implications for investment targeting and sustainable land use planning.
Keywords: 630; forestry plantations; large-scale land acquisitions; agricultural employment; remote sensing; agricultural yields